Vibrational excitation and dissociation of deuterium molecule by electron impact. (11th June 2021) - Laporta, V; Agnello, R; Fubiani, G; Furno, I; Hill, C; Reiter, D; Taccogna, F
Abstract: A theoretical investigation of electron-D2 resonant collisions—via the low-lying and the Rydberg states of D 2 − —is presented for vibrational excitation, dissociative electron attachment and dissociative excitation processes by using the local-complex-potential approach. Full sets of vibrationally resolved cross sections, involving the ground electronic state— X 1 Σ g + —and the first two electronic excited states— b 3 Σ u + and B 1 Σ u + —of the D2 molecule, are given for fusion plasma applications in their technologically relevant partially dissociated, detached divertor regimes. In particular, transitions between electronic excited states are also considered. Comparisons are made with cross sections present in the literature, where available.